Case Report: Cryoanalgesia for intractable thoracic pain due to chest wall tumor - Paim, Thays Sellan; Guernelli, Myrna; Simoneti, Rafael Soares; Miotto, André (Frontiers in Oncology, 2025)
IntroductionPostoperative pain in thoracic surgery is a major concern, often delaying recovery. Cryoanalgesia, using pressurized nitrous oxide, offers long-term pain relief by temporarily blocking peripheral nerve function. It takes effect within 72 hours, so an intercostal nerve block is used for immediate pain relief. Cryoanalgesia is effective for severe pain, with minimal side effects and no drug interactions.Case reportA 63-year-old man with severe thoracic pain, unresponsive to opioids, was diagnosed with a typical carcinoid tumor after a CT scan revealed lesions in his lung, thoracic wall, and adrenal gland. He underwent surgery for the thoracic lesions with cryoanalgesia, leading to excellent recovery and no pain. A month later, the adrenal lesion was removed laparoscopically. He remains pain-free and free of recurrence after one year, indicating successful treatment.ConclusionCryoanalgesia provides long-term relief for chest pain caused by tumors, with minimal side effects. It improves recovery and should be considered an essential part of pain management in thoracic surgery.